Interest Groups, Political Communication, and Jeffrey Alexander's Sociology of Power. (April 2015) - Nord, David Paul
This essay argues that Jeffrey Alexander's magnum opus, The Civil Sphere, presents a valuable but curiously narrow account of how political power works in American society, especially the power of interest groups. Alexander neglects the extensive literature on the "faces of power" in political science and the classic, critical literature on "source reporting" in journalism studies, both of which offer analyses of interest-group activity and discourse that are more compelling than Alexander's analysis. Using the example of religious interest-group politics, the essay suggests that the language a group employs is not so much a marker of membership in a "civil sphere, " as it is a strategic discourse of ordinary politics. The essay concludes by suggesting that Alexander's civil sphere may be simply a particular vocabulary of politics rather than a separate and independent social realm.